2014
DOI: 10.1177/0011000014535955
|View full text |Cite
|
Sign up to set email alerts
|

Results of Immersion Service Learning Activism With Peers

Abstract: Despite the emphasis on multicultural counseling competence and social justice in counseling psychology, the mechanisms behind building skills related to effective work remain elusive. This qualitative study explored the experiences of student-participants during a service learning course based on social justice principles in Belize. The researchers sought to inform how a non-traditional teaching methodology—immersion service learning activism—might affect these students’ development. The researchers used Cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 35 publications
3
27
0
Order By: Relevance
“…Ultimately, it opened the door to greater empathy, stronger relationships, and more sophisticated intellectually and emotionally tinged awareness of self, other, and context. This theme of Internal Grappling is consistent with prior research showing that graduate students engaged in advocacy training often report an "eyeopening" confrontation with privilege and oppression (Caldwell & Vera, 2010, p. 169), coupled with a range of powerful emotions (e.g., Goodman et al, 2014;Koch et al, 2014;Nilsson et al, 2011;Stewart-Sicking et al, 2013;Toporek & Worthington, 2014). Notably, these eye-opening experiences and subsequent internal struggles are starting points in many identity development theories (Erchull et al, 2009;Helms, 1995) as well as the theory of transformative learning.…”
Section: Integration With Existing Scholarshipsupporting
confidence: 85%
See 1 more Smart Citation
“…Ultimately, it opened the door to greater empathy, stronger relationships, and more sophisticated intellectually and emotionally tinged awareness of self, other, and context. This theme of Internal Grappling is consistent with prior research showing that graduate students engaged in advocacy training often report an "eyeopening" confrontation with privilege and oppression (Caldwell & Vera, 2010, p. 169), coupled with a range of powerful emotions (e.g., Goodman et al, 2014;Koch et al, 2014;Nilsson et al, 2011;Stewart-Sicking et al, 2013;Toporek & Worthington, 2014). Notably, these eye-opening experiences and subsequent internal struggles are starting points in many identity development theories (Erchull et al, 2009;Helms, 1995) as well as the theory of transformative learning.…”
Section: Integration With Existing Scholarshipsupporting
confidence: 85%
“…Yet the present study is unique in its articulation of how this struggle continues to drive learning about the self as an agent of social justice, fueling an advocate identity that persists beyond the training experience. In other words, it is not only a common feature of advocacy training (e.g., Koch et al, 2014), but is in fact a necessary driver of a developmental process.…”
Section: Integration With Existing Scholarshipmentioning
confidence: 99%
“…We chose to compare the CSL, experiential, and didactic pedagogies because each is widely used and because CSL (Burnett et al, 2004; Chao et al, 2017; Hipolito‐Delgado et al, 2011; Koch et al, 2014; K. A. Lee & Kelley‐Petersen, 2018; Midgett & Doumas, 2016; Midgett et al, 2016; Nilsson et al, 2011; Smith et al, 2014) and experiential (Greene et al, 2014; Kuo & Arcuri, 2014; Murphy et al, 2006; Seto et al, 2006) methods have been associated with CIT growth in the MCC (Sue et al, 1992). Furthermore, the experiential pedagogy has been associated with more CIT growth than comparison courses (Castillo et al, 2007; Cates et al, 2007; Dickson et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative outcomes derived from this study align with comparable studies, where researchers (Dickson et al, 2010; Kuo & Arcuri, 2014; Murphy et al, 2006) observed growth concluding an experiential multicultural counseling course in the areas of multicultural knowledge, awareness, and skills. However, researchers (Hipolito‐Delgado et al, 2011; Koch et al, 2014; Smith et al, 2014) who focused on multicultural competency growth in a CSL‐focused multicultural counseling course used primarily qualitative methods, which observed themes of attainment in multicultural knowledge, awareness, and skills, with Koch et al (2014) finding an additional theme of relationship. Our results indicated that all pedagogical approaches yielded growth of multicultural knowledge, awareness, and skills in the previously defined MCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation